Optimalisasi Tata Letak Lantai Produksi SNC PT. SEMB PEM - Santoso, Francisca Ovi; -, Felecia (Jurnal Titra, 2014)
Management PT. SEMB decided to moving warehouse outside plant, so that PT. SEMB PEM has to do re-layout. PEM warehouse temporary will be moved to first floor, second and third floor will be used for production area. Re-layout also change the concept of layout, from product family concept layout to process concept layout. process concept layout will be devided into 3 process, there are preparation area, main line area, and also back end area. Process layout makes finished goods closer to outgoing to be shipped to customer. We are interested to finding more effective layout for PT. SEMB PEM. we just calculationg moment based on flow and distance for method we used in this study. SNC is one of group product in PT. SEMB PEM which divided into two production floor before, become into one after re-layout. As the result, we found that our suggestion layout which based on product family concept layout better than others with 7851.47 as total moment which 34% more effective than new layout and 6% more effective than old layout. Total moment of old layout is 8316.38, and the new layout is 11972.53.